PENGARUH PENAMBAHAN ASBUTON BUTIR TERHADAP KARAKTERISTIK BETON ASPAL CAMPURAN PANAS - Madi Hermadi (Direktorat Bina Teknik Jalan dan Jembatan, 2006)
One of Asbuton technology utilization is to use Granular Asbuton as additive for hot mix asphalt pavement. By adding Granular Asbuton, the hot mix asphalt pavement will be more resistant to traffic load and deformation. To understand how the characteristic changes of hot mix asphalt pavement, in this research, Granular Asbuton was added around 0%, 4%, 7% and 10% to hot mix asphalt then these characteristic were tested. The result showed that the addition of Granular Asbuton can affect hot mix asphalt characteristic such as binder characteristic, density, voids (VMA, VIM, VFB), Marshall stability, flow, Marshall Quotient, and dynamic stability. Based on the partial correlation analysis, each characteristic has significant correlation. The result also showed that the optimum addition of Granular Asbuton is 7%.